Relevance of UNESCO Education for All Policy of Improving the Quality of Education in Lithuania - Gudynas, Pranas; Uginčienė, Eglė (Acta Paedagogica Vilnensia, 2006)
The paper focuses on the evaluation of the relevance of UNESCO Education for All (EFA) Dakar goal six (to improve the quality of education) for the education in Lithuania and the viability of applying recommendations of UNESCO education policy in improving the quality of education in Lithuania. Based on the data of the National Students' Achievements' Research carried out in the years 2003. 2004 and 2005, factors determining the quality of general education have been analysed. The factors are compared with the education quality determinants pointed out in UNESCO documents, i.e. high professional level of teachers, individualization in education, improvement of the quality of education, improvement of physical educational environment, reduction of the number of students per class. The basic conclusion drawn up in the paper is that improvement of quality of student achievement is essential both for basic and secondary education in Lithuania. Currently, student achievement rather insignificantly pertains to the physical educational environment at school. Results of the analysis do not give grounds to believe that students' achievements' might be shortly improved by reducing the number of students per class. Individualization in education, improvement of student evaluation in the process of education and developing teacher competence are considered to be perspective trends of the Lithuanian education policy.
Keywords: UNESCO; the quality of education; student achievement; education for all; education policy